Stanze dipinte. L'Inamoramento de Orlando come allegoria dell'Amicizia nella Sala del bacio nel Palazzo del Giardino a Parma. (3rd April 2019) - Monaco, Angelo Maria
ABSTRACT: The essay analyses the iconography of the sixteenth-century frescoes by the Mannerist painter Bertoja in the 'Sala del bacio' of the 'Palazzo del Giardino', Parma. The series is interpreted as an allegory on the humanist theme of 'Friendship', seen as a Boiardan, epic, and aristocratic topic by members of the so-called 'Republic of Letters', of which Ottavio Farnese, patron of the frescoes, was a prominent member. The frescoes provide evidence of the fortunes of Boiardo's poem beyond the limits of the period's illustrated editions, displaying a different dimension of the poem's visual reception.